Comportamiento Epizootiológico de Parásitos (gastrointestinales) en Perros (canis familiaris) en el Barrio San Felipe Norte de la Parroquia Eloy Alfaro del Cantón Latacunga. - León Troya, Jefferson Stalyn (2018)
The present investigation was carried out in San Felipe North neighborhood Latacunga canton, based on the determination of the epizootiological behavior of gastrointestinal parasites in domestic canines (canis familiaris) through coproparasitic analysis, to structure measures of prevention against zoonotic parasitic diseases, the number total of sampled animals were 150. The used technique was Sheather, each sample was mixed, sediment, transferred to vacoutainer tubes, repose for 30 minutes, and analyzed under a microscope. Results obtained, 62 animals were positive to parasites representing 41.33% and 88 animals were negative interpreted as 58.66%, in positive Ancylostoma C. with 36.66%, Toxocara Canis reflected 3.33%, Strongylus Estercolaris with 1.33%. Canines between 0-12 months, of them 9 had Ancylostoma which represents 6%, 2 positive that is 1.33% for Toxocara. Animals 1-5 years reflected 39 positive for Ancylostoma with 26%, 3 positives to Toxocara representing 2% and 2 positives to Strongyloides which is 1.33%. Canines older than 5 years, 7 positives representing 4.66 only for Ancylostoma. In the sex variable of the canines there were 49 positive cases for males, 42 cases of Ancylostoma, representing 28%, 5 positives for Toxocara, 3.33% and 2 positives for Strongyloides, with 1.33%. In females, positive parasites were 13 patients for Ancylostoma giving 8.66. Variable breed 2 positives were found for the small breed in the case of Ancylostoma caninum with 1.33%. For the median breed 59 positive, 55 cases for Ancylostoma caninum which is 36.66%, 2 positives to Toxocara 1.33 in the same way for Strongyloides with 1.33%. The results were translated into triptychs for their corresponding sociabilization and subsequent deworming